Performance of Structures in İzmir After the Samos Island Earthquake - Dönmez, Cemalettin; Yakut, A.; Sucuoǧlu, H.; Binici, B.; Canbay, E.; Dönmez, C.; Ilki, A.; Ay, B.Ö. (Springer, 2022)
The October 30, 2020 Earthquake caused unexpectedly significant damage in İzmir considering its distance to the city. This paper evaluates the recorded ground motions, summarizes the performance of structures affected from the earthquake with emphasis on the reasons of damage. A detailed damage assessment was carried out by the Earthquake Engineering Research Center of Middle East Technical University to compile data on the damage of RC and masonry buildings. It was observed that majority of the damage was concentrated in the Bayraklı district due to its peculiar soil properties where many 7–10 story mid-rise RC buildings suffered heavy damage and collapse. The level of amplified ground motions combined with deficiencies of apparently non-code compliant buildings exacerbated the damage. The main reasons of damage were mainly attributed to the presence of soft stories, lack of proper detailing, poor construction quality, presence of heavy overhangs, and hence significant lack of code-compliance in essence. The influence of infill walls on seismic performance of deficient and inadequate buildings was clearly seen in this earthquake. This paper also discusses seismic code requirements in effect and their influence on the observed building performance. The recorded ground motions were compared with the code spectra to evaluate the performance of the buildings. The code response spectra were found to be well above the recorded ground motion spectra at the sites where significant damage was observed. © 2021, The Author(s), under exclusive licence to Springer Nature B.V.
Keywords: Earthquake Damage; RC Building Deficiencies; Samos Earthquake; Site Effects; Turkish Seismic Codes